2022
DOI: 10.1021/acs.jafc.2c07299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilute Acid Pretreatment and Lignin Extraction Conditions on Lignin Properties and Suitability as a Phenol Replacement in Phenol-Formaldehyde Wood Adhesives

Abstract: Corn stover was subjected to dilute sulfuric acid pretreatment to assess the impact of pretreatment conditions on lignin extractability, properties, and utility as a phenol replacement in wood phenol-formaldehyde (PF) adhesives. It was identified that both formic acid and NaOH could extract and recover 60−70% of the lignin remaining after pretreatment and enzymatic hydrolysis under the mildest pretreatment conditions while simultaneously achieving reasonable enzymatic hydrolysis yields (>60%). The availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The results regarding reaction time are consistent with the results of 2% (w/v) NaOH treatment at 120 °C, removing 88.59% of CC lignin content [16]. Another study revealed 60~70% lignin recovery using formic acid-and NaOH-pretreated corn stover [39]. The longer the reaction time, the greater the yield of lignin extraction.…”
Section: Influences Of Time On the Ler Of Phrsupporting
confidence: 81%
See 1 more Smart Citation
“…The results regarding reaction time are consistent with the results of 2% (w/v) NaOH treatment at 120 °C, removing 88.59% of CC lignin content [16]. Another study revealed 60~70% lignin recovery using formic acid-and NaOH-pretreated corn stover [39]. The longer the reaction time, the greater the yield of lignin extraction.…”
Section: Influences Of Time On the Ler Of Phrsupporting
confidence: 81%
“…It is noteworthy that when extracting lignin from holocellulose (which includes cellulose and hemicellulose), the process may degrade hemicellulose and reduce yields of sugars in subsequent conversion. Thus, it is essential to depolymerize hemicellulose before optimizing the pretreatment process for lignin extraction in order to make the most use of the holocellulose and efficiently remove lignin [17,39]. Catalytic hydrogenation can also be employed to degrade hemicellulose into xylose and arabinose, which can then be further converted into alcohols and sugar alcohols, thereby maximizing the utilization of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several researchers have explored the possibility in which lignin completely replaces the phenol needed in the production of PF resin adhesive. Saulnier et al 113 pretreated corn stover with dilute sulfuric acid, and evaluated the influence of pretreatment conditions on the extractability, characteristics and utility of lignin as a substitute for phenol in wood PF adhesive. Lignin-based wood adhesive was prepared by replacing 100% phenol with lignin extracted from formic acid.…”
Section: Biomass In Wood Adhesivesmentioning
confidence: 99%
“…Acid–based catalysts such as HCl, H 2 SO 4 , HNO 3 , and CH 3 COOH are frequently used since they are inexpensive and may change the crystal structure of cellulose and degrade the hydrogen bonds among cellulose and units of glucose, producing lignocellulosic biomass less resistant. In enzymatic saccharification, it has been shown that good sugar yields can be obtained with the use of acid pretreatment . The lignin and hemicellulose sections of the biomass are the only parts of the biomass that are selectively subjected to acid pretreatment.…”
Section: Modification Of Ligninmentioning
confidence: 99%